Changes in involvement in homework throughout compulsory secondary education / Cambios en la implicación en los deberes escolares a lo largo de la Educación Secundaria Obligatoria. Issue 2 (3rd April 2017) - Regueiro, Bibiana; Valle, Antonio; Núñez, José C.; Rosário, Pedro; Rodríguez, Susana; Suárez, Natalia
Abstract: This paper analyses the changes found in students' involvement in homework throughout the four grade levels of compulsory secondary education in Spain (ages 12–15). It also analyses the relationship between the changes in students' involvement in homework throughout schooling and motivational and emotional variables related to homework. Findings indicated that: (a) the amount of homework completed and homework time management diminished slightly throughout the grade levels researched; however, this result is clearer in terms of the amount of homework completed; (b) prior academic achievement is significantly related to the variables associated with students' involvement in homework; (c) the motivational and affective variables researched explained statistically significant variance related to two of the three dependent variables associated with involvement in homework; and (d) the association between the motivational and affective variables and involvement in homework is lower.